The Be Our Ally Beat Smoking (BOABS) study, a randomised controlled trial of an intensive smoking cessation intervention in a remote aboriginal Australian health care setting - Marley, J.; Atkinson, D.; Kitaura, T.; Nelson, C.; Gray, Dennis; Metcalf, S.; Maguire, G. (BioMed Central Ltd, 2014)
Background: Australian Aboriginal and Torres Strait Islander peoples (Indigenous Australians) smoke at much higher rates than non-Indigenous people and smoking is an important contributor to increased disease, hospital admissions and deaths in Indigenous Australian populations. Smoking cessation programs in Australia have not had the same impact on Indigenous smokers as on non-Indigenous smokers. This paper describes the outcome of a study that aimed to test the efficacy of a locally-tailored, intensive, multidimensional smoking cessation program. Methods: A randomised controlled trial of Aboriginal researcher delivered tailored smoking cessation counselling during face-to-face visits, aiming for weekly for the first four weeks, monthly to six months and two monthly to12 months. The control (“usual care”) group received routine care relating to smoking cessation at their local primary health care service. Data collection occurred at enrolment, six and 12 months. The primary outcome was self-reported smoking cessation with urinary cotinine confirmation at final follow-up (median 13 (interquartile range 12–15) months after enrolment).Results: Participants in the intervention (n = 55) and usual care (n = 108) groups were similar in baseline characteristics, except the intervention group was slightly older. At final follow-up the smoking cessation rate for participants assigned to the intervention group (n = 6; 11%), while not statistically significant, was double that of usual care (n = 5; 5%; p = 0.131). A meta-analysis of these findings and a similarly underpowered but comparable study of pregnant Indigenous Australian women showed that Indigenous Australian participants assigned to the intervention groups were 2.4 times (95% CI, 1.01-5.5) as likely to quit as participants assigned to usual care. Conclusions: Culturally appropriate, multi-dimensional Indigenous quit smoking programs can be successfully implemented in remote primary health care. Intensive one-on-one interventions with substantial involvement from Aboriginal and Torres Strait Islander workers are likely to be effective in these settings. Trial registration: Australian New Zealand Clinical Trials Registry (ACTRN12608000604303).